2015
DOI: 10.1007/s12026-015-8726-1
|View full text |Cite
|
Sign up to set email alerts
|

Platelets modulate the immune response following trauma by interaction with CD4+ T regulatory cells in a mouse model

Abstract: CD4+ T regulatory cells (Tregs) play a pivotal role in the anti-inflammatory immune response following trauma. The mechanisms of CD4+ Treg activation are mostly unknown. Here, we hypothesize that platelets regulate CD4+ Treg activation following trauma. In a murine burn injury model (male C57Bl/6N mice), depletion of platelets or CD4+ Tregs was conducted. Draining lymph nodes, blood and spleen were harvested 2 h and 7 days after trauma. CD4+ Treg activation was measured using phospho- and conventional flow cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 43 publications
2
39
1
Order By: Relevance
“…CD4+ Tregs have been shown to be activated early after injury in a murine burn model (46). Furthermore, also using the murine burn model, we have earlier been able to demonstrate an interaction of CD4+ Tregs with platelets, this interaction being modulated by TNF-RII- and TLR4-dependent pathways (6, 7). In this study, regarding CD4+ Treg count, we saw an increasing number relative to all CD4+ lymphocytes during the observed time period (Figure 2A).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…CD4+ Tregs have been shown to be activated early after injury in a murine burn model (46). Furthermore, also using the murine burn model, we have earlier been able to demonstrate an interaction of CD4+ Tregs with platelets, this interaction being modulated by TNF-RII- and TLR4-dependent pathways (6, 7). In this study, regarding CD4+ Treg count, we saw an increasing number relative to all CD4+ lymphocytes during the observed time period (Figure 2A).…”
Section: Discussionmentioning
confidence: 79%
“…The detection of an interaction of CD4+ CD4+ Tregs with platelets in a murine burn model led us to investigate platelet function in this study on multiple trauma patients as well (6). Our thromboelastometric results show an increasing MCF both in the extem and fibtem measurements (Figures 4B,C); however, subtracting the fibtem MCF from the extem MCF, thereby calculating the platelet contribution or platelet MCF (41), we actually saw a decrease (Figure 4D).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelets have been previously described to interact with regulatory T cells under inflammatory conditions. In this context, it could be shown that platelets are needed to control the anti-inflammatory actions of CD4 + regulatory T cells following burn injury trauma in mice ( 156 ). In another organ, platelets have also been shown to interact with CD4 + T cells in the liver following ischemic injury and during atherosclerosis ( 157 , 158 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, platelets have antiinflammatory properties. Platelets are known to interact with and enhance responses of regulatory T cells, resulting in increased IL-10 levels (142,143). Regulatory T cells are needed to support macrophage efferocytosis via secretion of IL-13 during resolution of inflammation (144).…”
Section: Platelets In Resolutionmentioning
confidence: 99%